Peningkatan Keterampilan Berbicara Siswa Kelas Rendah melalui Metode Storytelling Berbasis Gerak dan Tari Tradisional - Nadia Bismi Hafifah; Claudia Marpaung; Aulia Atirka (Prodi Pendidikan IPS STKIP AL MAKSUM, 2026)
: Speaking skills are one of the crucial productive development achievements for low-grade students, but the reality at Mitra Schools shows that students tend to be passive, anxious, and have limited vocabulary due to conventional one-way learning. This community service aims to improve the speaking skills of low-grade students through an innovative learning model in the form of integrating storytelling methods with elements of local traditional movement and dance. The implementation method uses a participatory and collaborative partnership approach through four main stages: situation analysis, teacher competency workshops, integrated practice assistance (Small Storytelling Class), and monitoring and evaluation. The impact of the intervention was measured quantitatively through performance assessment instruments (pre-test and post-test). The results of the activity showed a massive and significant increase, where the average score of students' overall speaking skills jumped from 53.6 (poor category) at the pre-test to 84.4 (excellent category) at the post-test. The indicators of confidence and courage to perform experienced the highest increase of 30.8 points, proving that the synchronization of dance motor activities is able to suppress children's mental anxiety in front of the public naturally. In conclusion, the integration of movement-based storytelling methods and traditional dance is not only effective as a multisensory bridge to optimize children's fluency, intonation, expression, and vocabulary, but also strategic in preserving local culture and internalizing character values from an early age.